The Scorner's Seat: An Address - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "The Scorner's Seat: An Address," written by Walter B. Wriston for the Fletcher School of Law and Diplomacy on 30 September 1982. The original speech is located in MS134.001.005.00005.